2020
DOI: 10.2106/jbjs.st.19.00035
|View full text |Cite
|
Sign up to set email alerts
|

The Central-Splitting Approach for Achilles Insertional Tendinopathy and Haglund Deformity

Abstract: Background: Insertional Achilles tendinopathy causes posterior heel pain at the insertion of the Achilles tendon, often in combination with a calcaneal exostosis, or Haglund deformity. Insertional Achilles tendinopathy often presents with a posterior osseous prominence and leads to calcification of the Achilles tendon 1. Nonoperative treatment of these conditions includes activity modification, nonsteroidal anti-inflammatory agents, heel lifts, shoe modification, physical therapy focused on eccentric strengthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…A recent paper concluded that the MITA approach for IAT "appears to be safe and yields satisfactory results." 9 This is in line with previous studies, 3,8 but these had limited sample sizes (22-43 patients) and their conclusions were solely based on the mean PROM values. The reported ranges and standard deviations revealed that a considerable proportion of patients remain symptomatic.…”
Section: Discussionsupporting
confidence: 87%
“…A recent paper concluded that the MITA approach for IAT "appears to be safe and yields satisfactory results." 9 This is in line with previous studies, 3,8 but these had limited sample sizes (22-43 patients) and their conclusions were solely based on the mean PROM values. The reported ranges and standard deviations revealed that a considerable proportion of patients remain symptomatic.…”
Section: Discussionsupporting
confidence: 87%
“…11 Nonetheless, conservative therapy will fail in almost half of patients, especially those with retrocalcaneal bursitis and/or Achilles insertional tendinopathy. 11,19 Conservative therapy is considered failed if unresponsive after six months. Surgical management is the following line of treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…A sterile dressing was applied to the wound, and the leg was immobilized with a dorsal plaster splint or cast placed at 15-20o with the ankle in in the equinus position. The tourniquet was then deflated and the patient was placed in the supine position (13,17) . Non-functional immobilization was used during the postoperative period.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…From the sixth to the eighth week, the wedges were gradually removed and physical therapy was begun. Finally, the boot was removed after the eighth week (17) .…”
Section: Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation